THE EFFECT OF DISCIPLINE AND TRAINING ON JOB MOTIVATION AND IMPLICATION ON EMPLOYEE PERFORMANCE (STUDY CASE AT PT. VANIA INTERIOR FURNISHING) - Santika Maruhun; Chaerudin Chaerudin (Dinasti Publisher, 2019)
This research was conducted aiming to reveal how much the impact of Discipline, Training on Job Motivation and Implication of Employee Performance on employees working at PT Vania Interior Furnishing, using the PLS (Partial Least Square) method and structural equation analysis (SEM) based variants which can simultaneously conduct measurement model testing along with structural model testing. The results showed that: (1) There was a positive and significant influence on Discipline attitude towards Employee Performance at PT. Vania Interior Furnishing. (2) There is a positive and significant influence of Discipline on Employee Job motivation at PT. Vania Interior Furnishing. (3) There is a positive and significant influence of Job motivation on employee performance at PT. Vania Interior Furnishing. (4) There is a positive and significant effect of training on Employee Performance at PT. Vania Interior Furnishing. (5) There is a positive and significant effect of training on employee Job motivation at PT. Vania Interior Furnishing. (6) There is a positive and significant influence of Job motivation which mediates the effect of Discipline on Employee Performance at PT. Vania Interior Furnishing. (7) There is a positive and significant influence of Job motivation which mediates the effect of work training on employee performance at PT. Vania Interior Furnishing.